Aerogel Coating On The Copper Mesh As Superhydrophobic Porous Layer - Loganya, Supramaniam (Universiti Sains Malaysia, 2022)
Wastewater treatment using various separation techniques has become the focus of many researchers for some time now. There is an increase in the amount of oil used due to the escalating industrial development causing major harm to public health and environment. The lagging of the technical and management developments leading to oily wastewater pollution. Since the oil industry, oil refining, oil storage, transportation, and petrochemical industries in the production process produce a lot of oily wastewaters, treatment of oily wastewater sources becomes very broad. The conventional treatment methods include flotation, coagulation, biological treatment, and membrane separation technology (Yu et al., 2017). In view of this, a novel separation process using a superhydrophobic porous copper mesh filter was developed to separate the water from oil-water mixtures. In this study, aerogel was coated on the copper mesh via dip coating with the aerogel being dispersed in the ethanol and ethanol/water solution. Aerogel was also mixed into the PVDF polymer solution and cast on the copper mesh. Amongst the method, aerogel embedded within the PVDF solution offered the most uniform coating on the surface. Under this method, the other studied parameters include pore sizes of the copper mesh (500-mesh and 80-mesh sized meshes), aerogel concentration, and polymer (PVDF) concentration. The best filter was obtained on a 500-mesh sized coated with 15g PVDF+NMP+1g aerogel. The coated mesh exhibits low surface energy with the water contact angle of 150.40±2.31°. The average permeate flux for the pristine mesh and coated mesh are 218.91±3.85 and 351.90±3.93 L/m2.h respectively indicating that when the hydrophobicity increases, the 20 permeate flux of pure oil (heptane) also increases. However, the oil-water filtration efficiency for the coated mesh is lower than the pristine mesh which are 61.45% and 87.09% water rejection respectively. The filtration efficiency of the 15g PVDF+NMP+1g aerogel coated membrane is lower than that of the pristine mesh due to the pore sizes being reduced, thus, reducing the efficiency of the oil-water separation.